A step‐down protocol for omalizumab treatment in oral corticosteroid‐dependent allergic asthma patients. (1st December 2017) - Domingo, Christian; Pomares, Xavier; Navarro, Albert; Amengual, María José; Montón, Concepción; Sogo, Ana; Mirapeix, Rosa M.
Abstract : Aims: There are no specific criteria for a step‐down or withdrawal dose of omalizumab (OMA). Our purpose was to evaluate the viability of a protocol for OMAlizumab DOse REduction (the OMADORE study) in severe allergic asthma (SAA). Methods: The study population included 35 SAA patients treated during a minimum period of 1 year with oral corticosteroids (OC) equivalent to a mean daily dose of 4 mg of methyl‐prednisolone. To qualify for the protocol, the patients had to have received treatment with OMA for at least one and a half years, OC dose had to have reached the lowest tolerated dose and spirometry had to be greater than or equal to that at entry. The interventions were (a) OMA dose was reduced by half; (b) if patients were clinically stable after 6 months, the dose was halved again; (c) if repeated OC boosters were needed and/or spirometry worsened by more than 10%, OMA dose was raised to the previous figure until stabilization. Results: Mean age was 52.5 (17) years, median monthly OC dose was 120 (IQR: 225) mg. Pulmonary function: FVC: 79.7 (20.2)%; FEV1 : 64.8 (21.7)%; FEV1 / FVC: 61.7(13.8)%. OMA could be withdrawn in 34.3% of the patients; 22.9% tolerated a reduction, and in 42.9% the dose could not be modified. Follow‐up time after reduction or withdrawal ranged from 12 to 30 months. There were no severe exacerbations requiring emergency assistance or admission. Conclusions: The OMADORE study found that in more than 50% of SAA patients on OC, OMA dose can be safely reduced or withdrawn based on a progressive dose reduction protocol.